Analysis of Bone Marrow findings at Muhimbili National Hospital from 2006 to 2009 (Tanzania Medical Journal, 2015)
Background: Hematological disorders are among the major causes of morbidity and mortality in the world. The disorders are found to affect all people all over the world with increasing prevalence. However the pattern of these disorders in Tanzania is unknown. The study aimed at determining the frequencies of various haematological disorders as seen at Muhimbili National Hospital. Methodology: It was a retrospective descriptive study. A total of 1083 bone marrow reports were analyzed in the study. These included bone marrow reports for patients who were seen at Muhimbili National Hospital from 2006 to 2009. Results: Of all 1083 bone marrow reports analyzed, iron deficiency anemia was the most encountered non malignant disorder contributing 20.9%. This was followed by leukaemias; Acute lymphoblastic leukemia (7.6%), chronic myeloid leukemia (5.9%) and chronic lymphocytic leukemia (4.2%). Also 3.6% had megaloblastic anemia and 3.4% had aplastic anemia. Other disorders like multiple myeloma, Idiopathic thrombocytopenic purpura, myelodysplastic syndrome etc constituted relatively smaller percentages in comparison and contrast to the above mentioned disorders. The cumulative frequency of haemato-oncolgical disorders shows that they constitute the highest percentage of all diagnoses (29.0%). Conclusion and recommendations: The findings of the study showed the pattern of haematological disorders both malignant and non malignant. It was recommended that education should be provided to the public regarding haematological disorders especially iron deficiency anaemia and haemato-oncological disorders, and health services be improved for proper diagnosis and treatment of scrupulous patients.